Peripheral blood TCR repertoire improves early detection across multiple cancer types utilizing a cancer predictor - Tang, Yinglei; Liao, Xinyi; Liao, Bo; Peng, Dejun; Li, Qingbo (Frontiers in Oncology, 2025)
IntroductionIn the early asymptomatic stages of cancer, the immune system initiates a targeted response against tumor-associated antigens. During this phase, the immune system specifically identifies tumor antigens and triggers the clonal expansion of tumor antigen-specific T cells, which recognize tumor antigen peptides presented by the major histocompatibility complex via the T-cell receptor (TCR) on their surface. Consequently, monitoring alterations in the TCR repertoire holds promise for evaluating an individual’s immune status for cancer detection.MethodsIn this study, we introduced a deep learning framework named DeepCaTCR, designed to enhance the prediction of cancer-associated T-cell receptors. The framework employs a one-dimensional convolutional neural network with variable convolutional kernels, a bidirectional long short-term memory network, and a self-attention mechanism to facilitate feature extraction from amino acid fragments of varying lengths.ResultsDeepCaTCR demonstrates superior performance in cancer-associated TCR recognition, achieving an area under the receiver operating characteristic curve (AUC) of 0.863 and an F1-score of 0.669, thereby outperforming prevailing deep learning models. Validation result indicates that DeepCaTCR effectively distinguishes between tumor-infiltrating lymphocytes (TILs) and healthy peripheral blood samples, achieving an AUC greater than 0.95. It also exhibits high sensitivity (62.5%) and specificity (over 98%) in peripheral blood testing for early-stage cancer patients. To further enhance detection efficacy, we introduced a variance-based repertoire scoring strategy to quantify the dynamic heterogeneity of TCR clonal amplification, resulting in an increased AUC of 0.967 for pan-cancer early screening.DiscussionThis study introduces a novel tool for analyzing the tumor immune microenvironment, offering significant translational potential for early cancer diagnosis. Its key feature is a new scoring method based on variance, not the average method.